Методологія формування предметної області модифікаційних змін у важкому транспортному літаку - Dveirin, Oleksandr; Riabkov, Viktor; Kapitanova, Liudmyla; Kirnoson, Danylo (Avìacìjno-kosmìčna tehnìka ì tehnologìâ, 2023)
The subject of study is the process of forming the parameters of modification changes in a heavy transport aircraft. The goal is to develop the subject area of modification changes with the help of design models. The task is  to develop models for determining the parameters of modification changes of the base aircraft based on the subject area of the modification project, namely: a model of the decomposition of modification changes of the base aircraft with the selection of parameter levels, which made it possible to apply more reliable assessment methods for different groups of parameters; a model of displaying the structure of the base aircraft in the subject area of the modification project, which uses the concepts of similarity and equivalence, it allows to highlight the necessary modification changes of the base aircraft; a temporal model of tracking efficiency changes, taking into account the time interval of creating modifications; a model for assessing the feasibility of modification changes in lower-level parameters, taking into account additional labor costs for their implementation. All this makes it possible to increase the reliability of the technical and economic justification of the modification. The methods used are following: an analytical method of defining the subject area using a system of new criteria that allow evaluating the integral characteristics of the aircraft modification for the benefit of different participants at different stages of the creation of the modification: for project developers, specific cost criteria are adopted as the ratio of all types of costs to all useful work, performed by the modification at the stage of its operation; for the stage of flight tests and production development in modifications –  the criterion for the expediency of modification changes, taking into account the labor costs for their implementation; for operating airlines – the technology of formation of flight parameters, which provide a "niche" of competitiveness of modifications and temporary tariffs for the benefit of the consumer. The obtained scientific results: allow to form subject areas of promising modifications of heavy transport aircraft, which can reasonably compete in the world markets of aircraft and air transportation. Conclusion. The scientific novelty of the obtained results is as follows: the proposed model for determining the subject area of modification changes of the base aircraft. This makes it possible to set the parameters of modification changes in the aircraft at the stage of aircraft design, and thereby ensure its competitiveness in the aircraft and air transportation markets.